EP 7. The Burke–Fahn–Marsden Dystonia Rating Scale is age-dependent in healthy children. Issue 9 (September 2016) - Kuiper, M.; Vrijenhoek, L.; Brandsma, R.; Lunsing, R.; Burger, H.; Eggink, H.; Peall, K.; Contarino, M.F.; Speelman, J.; Tijssen, M.; Sival, D.
Abstract : Background: The Burke–Fahn–Marsden Dystonia Rating Scale (BFMDRS), involving a movement scale (BFMMS) and a disability scale (BFMDS), is a universally applied instrument for quantitative assessment of dystonia in children and adults. However, immature movements by healthy young children may also reveal "dystonic characteristics" as a consequence of physiologically incomplete brain maturation. In young dystonic children, an age-related effect could theoretically confound both the BFMMS and the BFMDS. Objective: In healthy young children, we aimed to determine whether physiologically immature movements and postures can induce an age-related effect on BFMMS and BFMDS scores. Methods: Nine assessors, specialized in movement disorders (3 adult-, 3 pediatric-neurologists and 3 MD/PhD students) independently scored BFMMS in 52 healthy children (4–16 years; 4 children/year of age; male/female = 1). In another 52 healthy children (4–16 years; 4 children/year of age; male/female = 1), parents scored their children's functional motor development according to the BFMDS. By regression analysis, we determined the association between BFMMS and BFMDS outcomes and age and compared the regression coefficients using the Z -test. Results: In healthy children, assessment of physiologically immature motor performances by the BFMMS and BFMDS revealed an association with age (until 16 and 12 years of age, β  = −0.72 and β  = −0.60, respectively (both p  < 0.001)). The unstandardized regression coefficients between BFMMS and BFMDS revealed no significant difference ( p  = 0.753). Conclusions: Both the quantitative BFMMS and the functional BFMDS are influenced by the age of the child in a similar pattern. For accurate interpretation of longitudinal BFMDRS scores in young dystonic children, consideration of pediatric age-relatedness appears advisor